2008
DOI: 10.1007/s11270-007-9584-9
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Pollution of the Quaternary Aquifer in Northern United Arab Emirates

Abstract: Natural conditions and human activities have caused serious quality degradation of the Quaternary aquifer in the north of the United Arab Emirates (UAE). The aquifer within Ajman City is unconfined, receiving limited recharge (12 542 m 3 / day) from the east and large pollutants flux (4,800 m 3 / day) from land surface. Field survey and laboratory analyses revealed anomalies in groundwater salinity (TDS), total hardness (TH), dissolved oxygen (DO), cations (Ca 2+ , Mg 2+ , Na + and K + ), anions (HCO À 3 , SO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The results of tests confirmed that leachate from the municipal landfill site under review constituted a source of contamination of the water environment, which was also shown by Kanownik and Policht-Latawiec (2016). Other researchers also proved the impact of municipal solid waste landfills on the deterioration of groundwater quality with varying degrees of pollution (Han et al 2016; Al-Hogaraty et al 2008).…”
Section: Discussionmentioning
confidence: 95%
“…The results of tests confirmed that leachate from the municipal landfill site under review constituted a source of contamination of the water environment, which was also shown by Kanownik and Policht-Latawiec (2016). Other researchers also proved the impact of municipal solid waste landfills on the deterioration of groundwater quality with varying degrees of pollution (Han et al 2016; Al-Hogaraty et al 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Seawater intrusion into the aquifer below the coastal area has been reported at depths as shallow as 1e2.5 m (Al-Hogaraty et al, 2008). Because the depth to water in our sampling sites ranged from 0.7 to 2.4 m, seawater could have contaminated the water collected at many of the sampling sites.…”
Section: Cod and Salinity At Each Sampling Site At Benowomentioning
confidence: 96%
“…With distance away from the mountainous areas, TDS concentration in groundwater increases and the groundwater becomes more saline (Figure 12). The dissolution of evaporates, leakage of saline water, and circulation of flow irrigation of the groundwater aquifer are also sources of TDS in groundwater [55][56][57][58][59][60][61]. However, population growth and density have a strong impact on TDS concentration in groundwater in the NUAE.…”
Section: (B)mentioning
confidence: 99%
“…The spatial relationship shows that the areas affected by high NO3 concentration and groundwater depletion are, at the same time, the areas that have the greatest need for water, including the irrigated agricultural areas (Figures 15 and 16). The impact of vegetation, as part of LULC, on groundwater recharge and groundwater level can be both negative and positive by facilitating the surface water infiltration and transpiration obtained from the rooted soil profile [61][62][63][64][65]. While the irrigated agricultural areas and water demand in the study area increase depletion in the groundwater level and the rate of evapotranspiration (2-3 m/year), the built-up areas decrease water infiltration and the recharge rate (< 4% /year) due to their impervious surfaces [12,13,66].…”
Section: Impacts Of Lulc Changes and Population Growth On Groundwater Levelmentioning
confidence: 99%
See 1 more Smart Citation